Floating Serv Ability Volleyball Skill: the Relationship of Muscle Strength for Junior High School - Nazirah, Nazirah (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. The purpose of this study was to determine the relationship between arm muscle strength and the results of the volleyball floating serve for students of Junior High School. Materials and methods. The form of this study is a correlation study with the population ofstudents of Junior High School, Kampar Regency with a total sample students. The instruments used in this study were the arm muscle strength test and the floating exercise. Results. Data analysis in this study obtained r count of 0.902 with a large contribution of 81.36%, this is classified as very good. Based on the results of the research conducted. Conclusions. Where obtained r arithmetic = 0.902>rtable=0.576 with a contribution of 81.36%. concluded that there is a relationship between arm muscle strength and the ability of the Junior High School to have a floating servi